Early hearing detection and hearing conservation training: An occupational health intervention for fishermen - Suryadi, Iwan; Fitriani, Nurlaila (Sociality: Journal of Public Health Service, 2025)
Occupational noise exposure represents a significant health risk for fishing communities, yet community-based preventive interventions for early detection and hearing conservation remain limited, particularly in coastal settings. Fishermen in Kelurahan Untia, Makassar City, are routinely exposed to high noise levels generated by boat engines and maritime work activities, increasing their risk of noise-induced hearing loss. This work aimed to improve fishermen’s occupational health through integrated early hearing detection and hearing conservation training. The intervention involved 50 participants, consisting of fishermen and family members from fishing households, particularly housewives, reflecting a family-based participatory approach. Program activities included education on occupational noise hazards and their impact on hearing health, assessment of noise exposure in fishing work environments, early hearing screening using the whisper test, and practical training on the use of hearing protection devices (earplugs). Program effectiveness was evaluated using a pre-test and post-test design to measure changes in participants’ knowledge regarding noise-related risks and hearing loss prevention. The results demonstrated a significant improvement in knowledge following the intervention, with 70% of participants reaching a high knowledge level compared with predominantly low baseline knowledge. Early hearing screening also identified a small proportion of participants with suspected mild hearing impairment who required further referral. These findings indicate that community-based early detection and hearing conservation training is feasible and effective in improving awareness and preventive behaviors among fishermen, and may contribute to reducing the long-term burden of noise-induced hearing loss and enhancing well-being in coastal communities.